Drought stress affects interactions between potato plants, psyllid vectors, and a bacterial pathogen. Issue 1 (23rd November 2022) - Cohen, Abigail; Basu, Saumik; Crowder, David W
Abstract: Transmission of insect-borne pathogens is mediated by interactions between insects and plants across variable environments. Water stress, for example, affects the physiology, defense, chemistry, and nutritional balance of plants in ways that alter their tolerance to herbivores and pathogens. However, few studies have explored interactions between water stress and insect-borne pathogens as well as the molecular mechanisms mediating these interactions. Here, we address these knowledge gaps by assessing effects of plant water stress on the transmission of a bacterial pathogen, Candidatus Liberibacter solanacearum (CLs), by the vector Bactericera cockerelli Šulc (potato psyllid). We hypothesized that plant water stress would promote pathogen transmission by inducing plant gene transcripts and phytohormones involved in defense. Our results showed water stress was associated with decreased CLs titer with two psyllid haplotypes. Our analysis of plant gene transcripts suggested water stress affected phytohormone pathways in ways that altered plant tolerance to the CLs pathogen. Our study shows that abiotic stressors like drought may mediate the spread of plant pathogens by altering plant signaling pathways in ways that affect pathogen transmission. Abstract : Water stress influences the transmission of an insect-vectored plant pathogen by altering the induction of plant gene transcripts involved in defense.